Adapting Violence Rehabilitation Programs for the Australian Aboriginal Offender - Day, Andrew (Journal of offender rehabilitation, 2000)
In this paper the authors address the question of how treatment and rehabilitation programs for violent offenders might be modified to more appropriately meet the needs of different cultural groups and improve treatment responsivity. The focus of the paper is on the needs of Aboriginal violent offenders in an Australian context, although the themes have relevance to treatment programs internationally. Two broad sources of information are used: the published literature relating to violent offending in Aboriginal people in Australia, and a small-scale interview-based qualitative survey of service providers with particular experience in this area. The evidence suggests there may be some distinctive features to Aboriginal violent offending. Suggestions are made on how programs can be more responsive to Aboriginal offender needs, thereby improving treatment and rehabilitation outcomes